LOX-1 as a biological marker and therapeutic target in cardiovascular pathology (literature review) - Amina M. Alieva; Irina E. Baykova; Elena V. Reznik; Natalia V. Teplova; Ramiz K. Valiev; Malika Kh. Gyzyeva; Albina B. Sultangalieva; Irina A. Kotikova; Natalia A. Novikova; Sergey A. Korvyakov; Igor G. Nikitin (ZAO "Consilium Medicum", 2024)
Cardiovascular diseases (CVD) are a global medical, social and economic problem. Currently, the search and study of new biological markers that can provide early diagnosis of CVD, serve as a laboratory tool for evaluating the effectiveness of treatment or be used as prognostic markers and criteria for risk stratification continues. The interest of scientists is focused on the study of the type 1 lectin-like receptor for oxidized low-density lipoproteins (LOX-1) as a diagnostic and prognostic marker in CVD. The presented literature review highlights the potential significance of the LOX-1 study as a diagnostic and prognostic laboratory tool in CVD. It is expected that future clinical and experimental studies will confirm the possibility of using LOX-1 as an additional non-invasive tool for diagnosis and prognosis assessment in patients with CVD. Modulation of LOX-1 levels and expression using pharmacological drugs may prove to be a promising direction for the treatment of CVD.